The effect of the siRNA-mediated downregulation of the non-integrin laminin receptor on cancer cell viability - Moodley, Kiashanee (My University, 2013)
Cancer is a hypernym used to describe a group of diseases characterised by the uninhibited growth and spread of abnormal cells in the body. An estimated 7.6 million annual deaths are attributed to the disease while 12.7 million new cases are reported every year. The severity of this disease demonstrates the urgent requirement of novel anti-cancer therapeutic agents. The non-integrin laminin receptor, here designated the 37 kDa/67 kDa laminin receptor (LRP/LR), is a multifunctional protein located on the surface, in the cytoplasm, in the perinuclear compartment and in the nucleus of cells. While this receptor is imperative for normal cellular functioning, it has also been implicated in many diseases – it serves as a cell surface receptor for numerous viruses, infectious prion proteins as well as certain respiratory tract pathogens. Additionally, LRP/LR has been found to have some involvement in zoonotic diseases and those involving neurodegeneration, such as Alzheimer’s disease. Most importantly for this study, LRP/LR has been implicated in cancer progression, where it was found to be overexpressed on the surface of various cancer cell lines, this overexpression correlating to increased metastasis. The aim of this study was to investigate the effect of the siRNA-mediated downregulation of LRP expression on the viability of tumorigenic lung and cervical cancer cells (A549 and HeLa, respectively). The cell surface LRP/LR and total LRP levels were investigated using flow cytometry and western blotting, respectively, in A549 and HeLa cells, the results revealing high percentages of both cell lines expressing LRP/LR on their surface. Additionally, A549 and HeLa cells express similar total levels LRP. The transfectability of these cells was confirmed and siRNA-LAMR1 was shown to significantly downregulate LRP expression (80% and 60% in A549 and HeLa cells, respectively). MTT assays revealed that the significant 13% and 18% reduction in cellular viability in A549 and HeLa cells, respectively, was as a consequence of LRP downregulation. This reduction in cellular viability was found to be a consequence of induced apoptosis (identified by the visualisation of the loss in nuclear integrity, as well as the significantly increased activity of the apoptosis-associated protein caspase- 3) and inhibited cellular proliferation in the aforementioned cells. These findings suggest that siRNA targeting LRP mRNA may act as a potential alternative therapeutic tool for the teatment of cancer.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2013
Keywords: Cancer cells.; Small interfering RNA.